Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/cjoc.202000483
|View full text |Cite
|
Sign up to set email alerts
|

The Real Structure of Pd(OAc)2 in Various Solvents

Abstract: Main observation and conclusion Pd(OAc)2 is an extensively utilized palladium source in the palladium initiated transformations either directly or as a catalyst precursor. However, the comprehension of the real structure of Pd(OAc)2 in solution is still vague. In this work, the structure of palladium acetate in solution was studied in detail by using X‐ray absorption fine structure (XAFS) spectroscopy. The results demonstrate that monomer is the main form for Pd(OAc)2 in the solution of 1,4‐dioxane, N,N‐dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…In the literature, Lei et al even investigated the structure of Pd(OAc) 2 in different solvents by using X-ray absorption fine structure (XAFS) spectroscopy. 37 They found that dissolving trimeric Pd 3 (OAc) 6 in MeCN solvent resulted in the breakup of its acetate bridge to generate the mainly monomeric Pd(OAc) 2 , which was similar to our observations. Remarkably, herein, adding Sc(OTf ) 3 to the MeCN-d 3 solution of Pd(OAc) 2 yielded only one single peak at δ H = 1.99 ppm, indicating that the methyl group of acetate from Pd(OAc) 2 had only one category of chemical environment, distinctly different from that for Pd (OAc) 2 alone in MeCN, and it was a more electron-deficient environment surrounding the methyl group when compared with the dominant peak at δ H = 1.96 ppm for Pd(OAc) 2 alone in MeCN-d 3 .…”
Section: Resultssupporting
confidence: 90%
“…In the literature, Lei et al even investigated the structure of Pd(OAc) 2 in different solvents by using X-ray absorption fine structure (XAFS) spectroscopy. 37 They found that dissolving trimeric Pd 3 (OAc) 6 in MeCN solvent resulted in the breakup of its acetate bridge to generate the mainly monomeric Pd(OAc) 2 , which was similar to our observations. Remarkably, herein, adding Sc(OTf ) 3 to the MeCN-d 3 solution of Pd(OAc) 2 yielded only one single peak at δ H = 1.99 ppm, indicating that the methyl group of acetate from Pd(OAc) 2 had only one category of chemical environment, distinctly different from that for Pd (OAc) 2 alone in MeCN, and it was a more electron-deficient environment surrounding the methyl group when compared with the dominant peak at δ H = 1.96 ppm for Pd(OAc) 2 alone in MeCN-d 3 .…”
Section: Resultssupporting
confidence: 90%
“…[26][27][28] In a specific investigation of the Pd(II) species in MeCN, Lei found that dissolving trimeric Pd 3 (OAc) 6 led its breaking up to generate the dominantly monomeric Pd(II) species, which may also benefit the formation of heterobimetallic Pd(II)/LA core in the presence of the LA source. [29] Herein, the linkage of the Sc 3 + cation to the Pd(II) species through diacetate bridge may have improved its electrophilic properties, thus improved its electrophilicity involved intramolecular hydroarylation reaction in the present studies, and facilitated the reaction happening in neutral dioxane solvent. As a result, using the strongly acidic medium such as trifluoroacetic acid to improve the electrophilicity of the Pd(II) species was avoided for this catalysis.…”
Section: Resultsmentioning
confidence: 73%
“…The reaction outcomes described in Figure can be explained in part by the findings of Lei and coworkers, who showed that monomerized trans -Pd­(OAc) 2 (solvent) 2 is liberated from Pd 3 (OAc) 6 in more polar solvents (evidenced by in operando X-ray absorption spectroscopy).…”
Section: Resultsmentioning
confidence: 86%